2019
DOI: 10.1061/(asce)gt.1943-5606.0001994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Shape on Stress-Dilatancy Responses of Medium-Dense Sands

Abstract: The effect of particle shape on the strength, dilatancy, and stress-dilatancy relationship was systematically investigated through a series of drained triaxial compression tests on sands mixed with angular and rounded glass beads of different proportions (0%, 25%, 50%, 75%, and 100%). A distinct overall regularity parameter was used to define the particle shape of these mixtures, which ranged from 0.844 to 0.971. The test results showed that all of the samples at an initial relative density of 0.6 exhibited st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 249 publications
(46 citation statements)
references
References 79 publications
2
44
0
Order By: Relevance
“…Particle shape can be characterized by three parameters, the aspect ratio ( R A ), convexity ( X C ), and sphericity ( C S ) (Yang and Luo 2015;Xiao et al 2019). These parameters were determined from binary images of two kinds of glass particles using ImageJ (Schneider et al 2012), as shown in Figs.…”
Section: Definition Of Particle Shapementioning
confidence: 99%
See 2 more Smart Citations
“…Particle shape can be characterized by three parameters, the aspect ratio ( R A ), convexity ( X C ), and sphericity ( C S ) (Yang and Luo 2015;Xiao et al 2019). These parameters were determined from binary images of two kinds of glass particles using ImageJ (Schneider et al 2012), as shown in Figs.…”
Section: Definition Of Particle Shapementioning
confidence: 99%
“…It should be noted that the aspect ratio, convexity, sphericity and overall regularity can only reflect the particle shape of a single particle but not an assembly of particles. Following the studies of (Yang and Luo 2015;Xiao et al 2019), 500 rounded particles were randomly selected for testing their particle shape parameters and the cumulative distribution curve for each particle shape parameter was obtained for the rounded particle assembly. The particle-shape cumulative distribution curve for the angular particle assembly was obtained in the same way.…”
Section: (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of particle size distribution on yield stress is complex and depends on the shape of the distribution curve since the interaction between different particle species affects the overall stress. Particles of more angular shape (polyhedral particles, for example) have an increased chance of interlocking, causing a more anisotropic contact force network and a larger yield stress . More significant stress fluctuations are observed for flatter particles compared to rounder and more prolate particles due to the occurrence of avalanche‐like slip events .…”
Section: Introductionmentioning
confidence: 99%
“…In geomechanics applications, DEM users commonly employ idealized spherical discrete elements to simulate granular grains due to the advantages this may offer, including easy contact detection and high computational efficiency . However, numerical studies have proven that grain shape underpins various facets of the mechanical responses for granular materials and should be properly accounted for in their modeling . Irregular shape of grains, for example, has been found attributable to the increase in particle rotation/rolling resistance, the enhancement of particle interlocking, and hereby the overall strength of a granular material, when compared with simulations with spherical particles .…”
Section: Introductionmentioning
confidence: 99%